Bilateral pneumothorax as possible atypical presentation of coronavirus disease 2019 (COVID-19) - Amrit S. Ahluwalia; Taha Qarni; Naureen Narula; Waleed Sadiq; Michel N. Chalhoub (Respiratory Medicine Case Reports, 2020)
Coronavirus disease 2019 (COVID-19) is most frequently associated with a mild presentation of fever, cough, and shortness of breath. Typical radiographic findings of COVID-19 are bilateral ground-glass opacities on computed tomography (CT) scans. However, there have been instances of pneumothorax, giant bulla, and pneumomediastinum, mainly in elderly COVID-19 patients and predominately occurring at least one week after symptom onset. Here, we report a case where a healthy, young Hispanic man presented with three days of fever, cough, and dyspnea. On admission to the emergency department, he was found to have bilateral pneumothoraces, pneumomediastinum, and pneumopericardium requiring bilateral chest tubes. The patient had no predisposing risk factors for pneumothorax, such as a history of trauma, smoking, past intubations, asthma, high pressure oxygen delivery, or a history of prior pneumothorax. The only positive diagnostic test was a SARS-CoV-2 test by real-time reverse transcriptase–polymerase chain reaction assay. This case highlights the potential atypical presentation of a COVID-19 infection and is the first reported case, to our knowledge, that features bilateral spontaneous pneumothoraces, pneumomediastinum, and pneumopericardium as a probable rare presentation of COVID-19.